Literature Review: Pengaruh Brain Gym Terhadap Tingkat Konsentrasi Belajar Pada Siswa Sekolah Dasar - Ainnurrahmah Kamila; Rika Harini; Ponirah Ponirah (Malahayati Nursing Journal, 2022)
ABSTRACT Learning is a process that students do to get change. Concentration is needed in the student learning process. The concentration ability of students can increase with the course of age and the ability to sort out the material. One way to increase concentration in students is to do a brain gym. Brain gym is an exercise method: that uses kinesis training with the whole brain through the renewal of closed movement patterns. Objective: The purpose of this literature review is to find out the description of the influence of the brain gym on the level of learning concentration in elementary school students. The method used is a literature review looking for articles from the internet with a range of 2010-2020 based on keywords set by google scholars. Results: Based on a literature review of 11 articles, 7 articles were found that met the established criteria. Results of the 7 articles explain that the brain gym can affect the level of student learning concentration as seen from the p-value = 0.00 to 0.008 which means the p-value = 0.05 for students. There is an effect of brain gym on the level of learning concentration in elementary school students. Suggestion: It is hoped that further researchers can apply brain gym directly to elementary school students Keywords: Elementary School Students, Brain Gym, Study Concentration  ABSTRAK Belajar adalah suatu proses yang dilakukan oleh siswa untuk melakukan suatu perubahan. Konsentrasi sangat dibutuhkan dalam proses belajar siswa. Kemampuan konsentrasi siswa dapat meningkat seiring bertambahnya usia dan kemampuan memilah materi. Meningkatkan konsentrasi pada siswa adalah dengan melakukan senam otak. Senam otak adalah metode latihan yang menggunakan latihan kinesis dengan seluruh otak melalui pembaharuan pola gerakan tertutup. Tujuan dari literature review ini adalah untuk mengetahui pengaruh senam otak terhadap tingkat konsentrasi belajar di sekolah dasar. Metode Penelitian yang digunakan adalah literature review dengan mencari artikel dari jaringan pada rentang 2010-2020 berdasarkan kata kunci yang ditetapkan oleh Google Scholar. Berdasarkan ulasan dari tinjauan pustaka dari 11 artikel ditemukan 7 artikel yang memenuhi kriteria yang ditetapkan. dari 7 artikel menjelaskan bahwa senam otak dapat mempengaruhi tingkat konsentrasi belajar siswa dilihat dari nilai p value = 0,00 sampai dengan 0,002 yang berarti nilai p value = 0,05 pada siswa. Ada pengaruh senam otak terhadap tingkat konsentrasi belajar pada siswa sekolah dasar diharapkan bagi peneliti selanjutnya dapat menerapkan senam otak secara langsung pada siswa sekolah dasar. Kata Kunci: Siswa Sekolah Dasar, Brain Gym, Konsentrasi Belajar